Pengaruh Kompensasi terhadap Kinerja melalui Disiplin Kerja sebagai Variabel Intervening pada Karyawan Honor Sekretariat DPRD Provinsi Jambi - Putri Wahyuni; Sumarni Sumarni; Wahyu Juari Setiawan (Jurnal Manajemen dan Ekonomi Kreatif, 2025)
This research aims to determine the effect of compensation on employee performance through work discipline as an intervention variable for honorary employees of the Jambi Province DPRD Secretariat. The analytical method used here is a quantitative descriptive analysis method. The population and sample are honorary employees of the Jambi Province DPRD Secretariat with a sample size of 69 employees. Data collection was carried out by distributing questionnaires with a Likert scale. The statistical analysis used is using the Structural Equation Modeling (SEM) technique, with Partial Least Square (PLS) as a creation tool using the SmartPLS program. The results of this research show that compensation has a positive and significant effect on employee performance, compensation has a positive and significant effect on work discipline, work discipline has a positive and significant effect on employee performance and compensation has a positive and significant effect on employee performance mediated by work discipline.